Creep or relaxation master curves calculated from experimental dynamic viscoelastic function - Rui Miranda Guedes (1998)
The problem treated consists in obtaining the unknown creep or relaxation master curves from experimental dynamic viscoelastic functions obtained on a DMTA analyser. In the present work, a general discrete model, the generalised Kelvin model or the generalised Maxwell model, is used to fit the complex compliance or the complex modulus, respectively. A linear regression technique is applied to the measured data in an iterative calculation, varying the relaxation or the retardation times to obtain the minimum of the relative error. For a physical meaning the admissible solutions do not include negative relaxation or retardation times. The method may be used to obtain an approximation of the discrete relaxation or retardation spectra from dynamic experimental data The error within this procedure is discussed.